Analytical Study of Urban Heat Spot Patterns in Colombo District from 1988 – 2019 based on Landsat Data - Saumya Chathuranga; Chandana Jayaratne (International Journal of Disaster Management, 2022)
Researching on urban heat island (UHI) is a hot topic among urban designers due to its adverse impacts. This paper focuses on studying spatial and temporal dynamicity of surface UHI in the Colombo district based on correlations between land surface temperatures (LST) with normalized difference vegetation index (NDVI) and normalized difference built-up index (NDBI) using Landsat data from 1988 to 2019. Image processing and statistical analysis were done using QGIS Desktop 3.16.0 and RStudio softwares respectively. The mean of LSTs were continuously increasing from 1988 to 2019. The highest LSTs were observed at the Colombo harbour area in both 1997 and 2007. After initiation of the port city project in 2015, these values have been increased rapidly around the Colombo port city area. The expansion of UHI area was 71.55% between 1988 to 2019, and they were distributed from the western coastal belt to the east along with the central part of the district. The urban hot spots (UHS) were compacted at harbour and port city area. Additionally, new hot spots have been generated since 2017 adjacent to “Seethagama”. These small pockets are too hot and not very conducive for human settlements. Parking lots, compacted built-up areas, and ongoing industrial construction areas influence the formation of UHS. Considering this critical situation, it is highly recommended that to move mitigation strategies like urban greening methods, cooling pavements and cooling roofs, etc.  These results could be used towards a well-designed urban planning system to maintain the ecological balance within the study area.